Multistep methods for coupled second order integro-differential equations: stability, convergence and error bounds - Lucas Jódar; José Luis Marera; Gregorio Rubio (International Journal of Mathematics and Mathematical Sciences)
In this paper multistep methods for systems of coupled second order Volterra integro-differential equations are proposed. Stability and convergence properties are studied and an error bound for the discretization error is given.